Nobody's fault? - Hermes, Patricia (New York : Harcourt Brace Jovanovich, 1981)
Emily likes to play baseball and tease her brother, but her happy life is interrupted when her brother has a fatal accident.
Keywords: Relationships -- Children's literature; Reaction -- Children's literature